Effect of green-based extraction approaches on antioxidant activity and phenolic compounds of Oregano (Origanum vulgare ssp. hirtum (Link) Ietswaart) - Christina Panagiotidou; Maria Irakli; Elisavet Bouloumpasi; Paschalina Chatzopoulou (Phytochemistry Letters, 2025)

Fortification of wheat bread with an alternative source of bean proteins using raw and roasted Phaseolus coccineus flours: Impact on physicochemical, nutritional and quality attributes - Irene Bosmali; Kali Kotsiou; Anthia Matsakidou; Maria Irakli; Panagiotis Madesis; Costas G. Biliaderis (Food Hydrocolloids, 2025)

Automatic segmentation of radar data from the Chang’E-4 mission using unsupervised machine learning: A data-driven interpretation approach - Iraklis Giannakis; Ciaran McDonald; Jianqing Feng; Feng Zhou; Yan Su; Javier Martin-Torres; Maria-Paz Zorzano; Craig Warren; Antonios Giannopoulos; Georgios Leontidis (Icarus, 2024)

Valorizing apple pomace as stabilizer of olive oil-water emulsion used for reduction of saturated fat in biscuits - Vasileia Sereti; Kali Kotsiou; Liliana Ciurlă; Antoanela Patras; Maria Irakli; Athina Lazaridou (Food Hydrocolloids, 2024)

Bruchid Infestation Was Associated With Agronomic Traits in Field-grown Faba Bean Genotypes - Ioannis T. Tsialtas; Maria Irakli (Journal of Crop Health, 2024)
Bruchus rufimanus , a univoltine seed weevil (bruchid), can cause severe seed yield and quality losses in faba beans restricting crop profitability and expansion. Chemical insecticide applications have been reported of low effectiveness and thus, growing genotypes tolerant to bruchid has been suggested as an alternative. Ten faba bean ( Vicia faba L.) accessions belonging to three varieties (var. major (seven accessions), var. minor (two accessions), var. equina (one accession)) were tested under field conditions for two growing seasons. Agronomic and seed traits were determined in an attempt to associate any tolerance to bruchid with easily-assessible, highly-heritable characters in order to be used as indirect selection criteria. The genotypes varied in bruchid tolerance (percentage of bruchid emergence holes (BD), percentage of endoparasitoid ( Triaspis thoracica ) emergence holes and bruchid infestation level (BI = BD + PD)), agronomic traits and seed properties. The dark-colored, small- and medium-seeded accessions (var. minor and var. equina ), commonly used for feed, had the lowest BI (4.21–8.17%) ranging below the limit of 10% set as the highest acceptable for using faba beans as feed. Large-seeded accessions (var. major ), which had light-colored seed coat (testa) with yellow hue, showed BI from 11.80% up to 24.54%, far-above the limit of 3% for seeds used as food. Apart from the seed size and color, susceptible genotypes had more seeds per pod, less pods and less branches per plant, possibly offering an easy access to females for laying more eggs on the limited number of pods, albeit the more space and food (higher protein content per seed) they offer to the developing larvae. Phenols and tannins in seeds, a putative chemical defense mechanism against bruchid, did not associate with the percentage of bruchid- or endoparasitoid-damaged seeds. Concluding, certain plant architectural traits and seed properties related to bruchid infestation in faba beans can be used as useful tools to select tolerant genotypes.

Influence of sesame cake on physicochemical, antioxidant and sensorial characteristics of fortified wheat breads - Chrysanthi Nouska; Maria Irakli; Prokopis Palakas; Anastasia E. Lytou; Elisavet Bouloumpasi; Costas G. Biliaderis; Athina Lazaridou (Food Research International, 2024)

Evidence of shallow basaltic lava layers in Von Kármán crater from Yutu-2 Lunar Penetrating Radar - Iraklis Giannakis; Javier Martin-Torres; Yan Su; Jianqing Feng; Feng Zhou; Maria-Paz Zorzano; Craig Warren; Antonios Giannopoulos (Icarus, 2024)

Stochastic hyperbola fitting, probabilistic inversion, reverse-time migration and clustering: A novel interpretation toolbox for in-situ planetary radar - Iraklis Giannakis; Javier Martin-Torres; Maria-Paz Zorzano; Yan Su; Craig Warren; Antonios Giannopoulos (Icarus, 2023)

In vitro and in vivo glycemic responses and antioxidant potency of acorn and chickpea fortified gluten-free breads - Ippolyti Gkountenoudi-Eskitzi; Kali Kotsiou; Maria N. Irakli; Antonios Lazaridis; Costas G. Biliaderis; Athina Lazaridou (Food Research International, 2023)

Presence of mycotoxins, heavy metals and nitrate residues in organic commercial cereal-based foods sold in the Greek market - Adriana Skendi; Maria Papageorgiou; Maria Irakli; Dimitris Katsantonis (Journal of Consumer Protection and Food Safety, 2020)

Ex situ evaluation of seed quality and bruchid resistance in Greek accessions of red pea (Lathyrus cicera L.) - Ioannis Τ. Tsialtas; Georgia S. Theologidou; Fotis Bilias; Maria Irakli; Athina Lazaridou (Genetic Resources and Crop Evolution, 2020)

Development and Characterization of a Self-Nanoemulsifying Drug Delivery System Comprised of Rice Bran Oil for Poorly Soluble Drugs - Georgios K. Eleftheriadis; Panagiota Mantelou; Christina Karavasili; Paschalina Chatzopoulou; Dimitrios Katsantonis; Maria Irakli; Aggeliki Mygdalia; Ioannis S. Vizirianakis; Dimitrios G. Fatouros (AAPS PharmSciTech, 2019)

Traits related to bruchid resistance and its parasitoid in vetch seeds - Ioannis Τ. Tsialtas; Maria Irakli; Athina Lazaridou (Euphytica, 2018)

Evaluation of a durum wheat selection scheme under Mediterranean conditions: adjusting trial locations and replications - Demetrios Baxevanos; Evangelos Korpetis; Maria Irakli; Ioannis Τ. Tsialtas (Euphytica, 2017)

Occurrence, Origin and Transformation Processes of Geogenic Chromium in Soils and Sediments - Maria Chrysochoou; Elina Theologou; Nefeli Bompoti; Dimitris Dermatas; Iraklis Panagiotakis (Current Pollution Reports, 2016)

Responses of mirror neurons in area F5 to hand and tool grasping observation - Magali J. Rochat; Fausto Caruana; Ahmad Jezzini; Ludovic Escola; Irakli Intskirveli; Franck Grammont; Vittorio Gallese; Giacomo Rizzolatti; Maria Alessandra Umiltà (Experimental Brain Research, 2010)